Oogenesis in Shabout Barbus grypus Heckel , 1843 (Baghdad Science Journal, 2025)
The female Shabout were collected as samples from Dijla river in Baghdad. The oocyte developmental stages were divided in to nine stages, based on nucleus structure , cellular inclusions and ovarian follicle structure ,they are:-( Oogonia stage , Early Perinucleolar Stage , Advanced Perinucleolar Stage , Cortical Alveoli Stage , Primary Yolk Stage , Secondary Yolk Stage , Tertiary Yolk Stage , Migratory Nucleus Stage , Hydration Stage(